Remittances and asset accumulation in Bangladesh: A study using generalized propensity score - Mehdi Chowdhury; Dragana Radicic (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2018)
Drawing on a sample of households in Bangladesh, we utilize the Generalized Propensity Score (GPS) method to investigate the impact of internal and international remittances on households' net assets. The analysis suggests an inverted U shaped relationship between the amount of internal remittances and net assets. Concerning the effect of international remittances on net assets, the results do not indicate a clear cut relationship between international remittances and assets. The paper also indicates not only the source but also the size of remittances has a role to play in the utilization.
Keywords: D01; F24; O53; 330; Remittances; Bangladesh; Assets; Generalized Propensity Score